Diagnosis and Treatment of Aspergillosis - Harliza, Baiq Fanindya; Fathana, Prima Belia (Jurnal Biologi Tropis, 2024)
Aspergillosis is an infection caused by the fungus Aspergillus , which typically affects individuals with weakened immune systems. One of the more serious forms of this infection is chronic pulmonary aspergillosis, which has a mortality rate of over 50%. This infection is estimated to affect approximately 3 million people worldwide, making it a significant global health issue. Accurate diagnosis and effective management are crucial to reducing morbidity and mortality. This article aims to explore the diagnosis and management of aspergillosis. The method employed is a literature review, with data obtained from various scientific articles through databases such as PubMed, Google Scholar, and ScienceDirect, with a publication limit of the last 10 years. Diagnosis of aspergillosis is based on clinical manifestations and supported by laboratory, radiological, and mycological examinations. Management of aspergillosis includes the administration of oral corticosteroids, antifungal drugs, surgery, and immunomodulatory therapy. Diagnosis is established based on clinical symptoms and relevant supporting examinations, while treatment is adjusted according to the severity of the infection and the patient's overall health condition. The conclusion of this article emphasizes the importance of early diagnosis and appropriate management in reducing the mortality rate associated with aspergillosis.